1991
DOI: 10.1161/01.res.69.2.530
|View full text |Cite
|
Sign up to set email alerts
|

Human nonmuscle myosin heavy chains are encoded by two genes located on different chromosomes.

Abstract: We report the cloning of cDNAs encoding two different human nonmuscle myosin heavy chains designated NMMHC-A and NMMHC-B. The mRNAs encoding NMMHC-A and NMMHC-B are both 7.5 kb in size but are shown to be the products of different genes, which are localized to chromosome 22q11.2 and chromosome 17p13, respectively. In agreement with previously reported results using avian tissues, we show that the mRNAs encoding the two myosin heavy chain isoforms are differentially expressed in rat nonmuscle and muscle tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
189
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(193 citation statements)
references
References 46 publications
3
189
0
1
Order By: Relevance
“…Its heavy chain has three isoforms in mice, including Myh9, Myh10 and Myh14, among which Myh9 accounts 480% of the total 7,8 . Recent studies revealed that dissociation-induced actin-myosin contraction caused the apoptosis of embryonic and induced-pluripotent stem cells [9][10][11] .…”
mentioning
confidence: 99%
“…Its heavy chain has three isoforms in mice, including Myh9, Myh10 and Myh14, among which Myh9 accounts 480% of the total 7,8 . Recent studies revealed that dissociation-induced actin-myosin contraction caused the apoptosis of embryonic and induced-pluripotent stem cells [9][10][11] .…”
mentioning
confidence: 99%
“…KIAA0454 encodes a nonmuscle myosin heavy chain A (NMMHC-A)-like protein which might play a role in smooth muscle cell proliferation. 30,31 The related 1q21.1 sequence showed 97% identity at a nucleotide level and 97% identity at an amino acid level with KIAA0454. However, the 1q21.1 sequence did not have any representative ESTs in dbEST as determined by BLASTN analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is a major cytoskeletal protein, which is found in the contractile apparatus in muscle cells as well as in nonmuscle cells. In smooth muscle tissue, protein and molecular data provide evidence for two smooth muscle myosin heavy chains (MHCs), designated as SM1 and SM2, approximately 204 kDa and 200 kDa, respectively, which are the products of alternate mRNA splicing differing in their carboxy termini [2,21,23,30], and two non-muscle MHCs, designated as NMA and NMB, approximately 196 kDa and 198 kDa, respectively [13,14,16,27].…”
Section: Methodsmentioning
confidence: 99%
“…Two pairs of primers taken from the sequence of the human non-muscle type A cDNA (nt 1164 and 1935) and type B cDNA (nt 980 and 1751), one pair from each [27], were synthesized using a DNA synthesizer. The nucleotide sequences of RANMMHCA and RANMMHCB were determined by the dideoxy-chain termination method [25] and are available through DDJB (GenBank/EMBL) Access Number D63693 and D63694.…”
Section: Methodsmentioning
confidence: 99%